2009
DOI: 10.1166/jnn.2009.ns83
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Procedure to Obtain Nanocrystalline Diamond/Porous Silicon Composite by Chemical Vapor Deposition/Infiltration Processes

Abstract: Nanocrystalline diamond (NCD) films were formed on porous silicon (PS) substrate by Chemical Vapor Deposition/Infiltration (CVD/CVI) process using a hot filament reactor. This innovative procedure is determinant to grow a controlled three-dimensional diamond structure with diamond grains formation in the pores, covering uniformly the different growth planes. In this CVI process, a piece of reticulated vitreous carbon (RVC) was used, under de PS substrate, as an additional solid source of hydrocarbon that ensur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The coating consisted of uniform Mg grains with size of about 1 μm. It was reported that the grain size was controlled by the deposition pressure of the total reactor42. At a low pressure (P Ar  = 10 −2  MPa) it would yield a higher nucleation rate, which resulted in a higher number of grains but of a smaller size.…”
Section: Resultsmentioning
confidence: 99%
“…The coating consisted of uniform Mg grains with size of about 1 μm. It was reported that the grain size was controlled by the deposition pressure of the total reactor42. At a low pressure (P Ar  = 10 −2  MPa) it would yield a higher nucleation rate, which resulted in a higher number of grains but of a smaller size.…”
Section: Resultsmentioning
confidence: 99%
“…Common routes to generate mp-Si include electrochemical etching, metal-assisted chemical etching, chemical vapor deposition, , and metallothermic reduction. , Of these, metallothermic reduction using Mg metal offers a scalable and straightforward route to prepare mp-Si using inexpensive raw materials such as rice husks, bamboo, sand, glass, and diatoms. ,,, Magnesiothermic reduction is an exothermic redox reaction between Mg metal and SiO x . The reaction is typically performed at the melting point of Mg metal (650 °C) with temperature held constantly at this point to assist in the diffusion of the atoms in the solid state.…”
Section: Introductionmentioning
confidence: 99%
“…Common routes to generate mp-Si include electrochemical etching, 15−17 metal-assisted chemical etching, 18 chemical vapor deposition, 19,20 and metallothermic reduction. 3,21−27 Of these, metallothermic reduction using Mg metal offers a scalable and straightforward route to prepare mp-Si using inexpensive raw materials such as rice husks, bamboo, sand, glass, and diatoms.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The utility of porous Si is highly dependent on its surface area, crystallinity, morphology, and pore volume, which are often dictated by the synthetic methods used for its preparation. Porous Si can be made by top‐down approaches such as electrochemical etching and metal‐assisted chemical etching or bottom‐up approaches such as chemical vapor deposition, carbothermal reduction, and metallothermic reduction . Among these methods, metallothermic reduction has gained significant attention as it allows for straightforward synthesis of porous Si from inexpensive precursors such as glass, sand, or sol–gel polymers .…”
Section: Introductionmentioning
confidence: 99%